Critical Findings for Tunnel Functional Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Road tunnels employ a multitude of functional systems that include a variety of equipment: lighting, ventilation, power supply, fire protection systems such as fixed fire-fighting systems, fire detection systems, communications systems and operational devices, supervisory control and data acquisition, closed circuit television, variable message signs, and radio. Maintenance of these systems is critical to the operation of the tunnel and to the overall roadway network. NCHRP Synthesis 607: Critical Findings for Tunnel Functional Systems, from TRB's National Cooperative Highway Research Program, documents methods and practices employed by state departments of transportation (DOTs) and how DOTs define critical findings, the specific criteria they employ in identifying critical findings, and the processes they follow to address these systems-related issues.
Keywords: Transportation and Infrastructure

Childhood Cancer and Functional Impacts Across the Care Continuum - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Since the late 1960s, the survival rate in children and adolescents diagnosed with cancer has steadily improved, with a corresponding decline in the cancer-specific death rate. Although the improvements in survival are encouraging, they have come at the cost of acute, chronic, and late adverse effects precipitated by the toxicities associated with the individual or combined use of different types of treatment (e.g., surgery, radiation, chemotherapy). In some cases, the impairments resulting from cancer and its treatment are severe enough to qualify a child for U.S. Social Security Administration disability benefits. At the request of Social Security Administration, Childhood Cancer and Functional Impacts Across the Care Continuum provides current information and findings and conclusions regarding the diagnosis, treatment, and prognosis of selected childhood cancers, including different types of malignant solid tumors, and the effect of those cancers on children’s health and functional capacity, including the relative levels of functional limitation typically associated with the cancers and their treatment. This report also provides a summary of selected treatments currently being studied in clinical trials and identifies any limitations on the availability of these treatments, such as whether treatments are available only in certain geographic areas.
Keywords: Health and Medicine

Next Steps for Functional Genomics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
One of the holy grails in biology is the ability to predict functional characteristics from an organism's genetic sequence. Despite decades of research since the first sequencing of an organism in 1995, scientists still do not understand exactly how the information in genes is converted into an organism's phenotype, its physical characteristics. Functional genomics attempts to make use of the vast wealth of data from "-omics" screens and projects to describe gene and protein functions and interactions. A February 2020 workshop was held to determine research needs to advance the field of functional genomics over the next 10-20 years. Speakers and participants discussed goals, strategies, and technical needs to allow functional genomics to contribute to the advancement of basic knowledge and its applications that would benefit society. This publication summarizes the presentations and discussions from the workshop.
Keywords: Biology and Life Sciences

Functional Assessment for Adults with Disabilities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. Social Security Administration (SSA) provides disability benefits through the Social Security Disability Insurance (SSDI) and Supplemental Security Income (SSI) programs. To receive SSDI or SSI disability benefits, an individual must meet the statutory definition of disability, which is "the inability to engage in any substantial gainful activity [SGA] by reason of any medically determinable physical or mental impairment which can be expected to result in death or which has lasted or can be expected to last for a continuous period of not less than 12 months." SSA uses a five-step sequential process to determine whether an adult applicant meets this definition.
Keywords: Health and Medicine

Incorporating ADA and Functional Needs in Emergency Exercises - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 90: Incorporating ADA and Functional Needs in Emergency Exercises explores how airports include persons with disabilities and others with access or functional needs (DAFN) into emergency exercises. Because not all functional needs are visually or readily apparent, airports find that including these community members in DAFN on emergency exercises improves the safety of passengers, airport visitors, and employees at airports. The report describes effective practices and provides additional resources and tools in the following report appendices:Appendix A: Script for InterviewsAppendix B: ParticipantsAppendix C: DAFN-Inclusive Exercise Scenario from MSPAppendix D: Sample DAFN-Inclusive Training Materials from LAXAppendix E: ADA-Inclusive Exercise Worksheet from JAXAppendix F: List of Resource Groups to Involve in DAFN-Inclusive Emergency Planning and ExercisesAppendix G: Checklist for Integrating the DAFN Community in Emergency Exercises
Keywords: Transportation and Infrastructure

Building a More Sustainable, Resilient, Equitable, and Nourishing Food System: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Food Forum of the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop on July 22-23, 2020 that explored integration of the health, societal, economic, and environmental effects and future needs of the food system. The main objective of the workshop was to understand how to achieve a more sustainable, resilient, equitable, and nourishing food system. The workshop covered a number of topics, including new expectations for the food system within three dimensions of the food system (vulnerabilities, resiliency, and transformation). Discussions also covered global change, access to nutritious food, resiliency in complex dynamic systems and resiliency for the future, and consumption- and production-oriented strategies for transforming the food system. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Supporting Cross-Sector Partnerships for Food Security and Sustainability: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
According to the United Nations Food and Agriculture Organization's report, "State of Food Security and Nutrition in the World," between 702 and 828 million people were affected by hunger in 2021 - and projections indicate that by 2030, 670 million people will still be experiencing hunger. Gains in agricultural productivity over the past 60 years have increased the availability of food globally, but much more needs to be done. Even these gains were not made without expense; biodiversity loss, chemical runoff, water scarcity, soil degradation, and greenhouse gas emissions from food and agriculture industries, among other issues, have had extensive impacts on the health of natural and human systems during this time. While millions suffer from food insecurity, a large percentage of food is lost or wasted across the global supply chain. Addressing the multifaceted challenges of feeding a world under pressure from severe food insecurity, malnutrition, climate change, population growth, conflict, migration, and economic disruption will require transformative change to global food systems. To discuss opportunities for supporting research and innovation to address global agricultural and human health challenges associated with the compounding pressures of producing more food, more nutritiously, and with less environmental impact, the Government-University-Industry Research Roundtable of the National Academies of Sciences, Engineering, and Medicine convened a workshop for its membership and invited guests on February 16, 2022. This publication summarizes the presentations and discussion of the workshop.
Keywords: Food and Nutrition; Agriculture; Policy for Science and Technology

Assessing Intake of Food and Dietary Supplements in Older Adults: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Dietary assessment in older adults presents many unique problems due to the diversity of health states and capabilities that span the population group. Little is known about dietary intakes, body composition, and nutritional status among individuals 75 and older. The National Academies Food and Nutrition Board hosted a virtual workshop series in spring 2022 intended to provide guidance to researchers and clinicians. The workshops aimed to outline considerations relating to different methods of assessing intakes of food and dietary supplements in older adults. The covered topics included current status of dietary and nutrition assessment of older adults and advances and key issues in this topic; nutritional screening of older adults; and nutritional practices, challenges, and policies that affect older adults. This Proceedings highlights presentations and discussions from the workshops.
Keywords: Food and Nutrition

A Consumer Food Data System for 2030 and Beyond - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Patterns of food consumption and nutritional intake strongly affect the population's health and well-being. The Food Economics Division of USDA's Economic Research Service (ERS) engages in research and data collection to inform policy making related to the leading federal nutrition assistance programs managed by USDA's Food and Nutrition Service. The ERS uses the Consumer Food Data System to understand why people choose foods, how food assistance programs affect these choices, and the health impacts of those choices. At the request of ERS, A Consumer Food Data System for 2030 and Beyond provides a blueprint for ERS's Food Economics Division for its data strategy over the next decade. This report explores the quality of data collected, the data collection process, and the kinds of data that may be most valuable to researchers, policy makers, and program administrators going forward. The recommendations of A Consumer Food Data System for 2030 and Beyond will guide ERS to provide and sustain a multisource, interconnected, reliable data system.
Keywords: Food and Nutrition; Behavioral and Social Sciences

Global Food Security and Sustainability Implications of the Ukraine Conflict: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On June 1, 2022, the National Academies of Sciences, Engineering, and Medicine convened a public workshop to discuss global food security challenges arising from the Ukraine conflict and possible approaches to address these challenges. The workshop focused on short-term responses to the current crisis, opportunities for international collaborations, and how the crisis could impact U.S. national security interests in a changing climate, including the relationships between agricultural production, climate change, and security. Discussions also addressed connections among areas such as agricultural production, land use, energy, water, health, and biodiversity critical to promoting long term sustainability. This publication highlights the presentations and discussion of the workshop.
Keywords: Conflict and Security Issues

Creating the Future Workforce in Food, Agriculture, and Natural Resources: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The production of food and other agricultural goods is a fundamental human endeavor and a cornerstone of the U.S. economy. While careers related to agriculture and natural resources have evolved in response to new knowledge and technology, consumer demands, and environmental changes, these professional fields now face a critical challenge: the ability to recruit and maintain a robust workforce. Companies, government bodies, and research organizations involved in food, agriculture, and natural resources (areas referred to collectively as FANR) are struggling to attract the next generation of workers. This shortage is apparent in employment projections for both trade positions attainable with certificate programs and high-tech positions requiring advanced degrees. Factors such as an increasingly diverse population, shifting work and career views, and lucrative job opportunities in other fields impact the ability to recruit talented individuals into the agricultural workforce. To provide a forum for discussing how the community might come together to address this challenge, the National Academies of Sciences, Engineering, and Medicine held a workshop on February 10-11, 2016, in Washington, DC. There were approximately 100 participants from land-grant universities, non-land-grant universities, minority-serving universities, community colleges, high schools, professional societies, government bodies, and corporations - reflecting the wide diversity of organizations with a stake in the future FANR workforce. The workshop was designed not only to highlight the significance of the challenges but also to surface concrete, forward-looking opportunities for action. This Proceedings of a Workshop summarizes plenary presentations from the workshop along with insights from 10 working groups that described key challenges, ongoing efforts to address them, and promising approaches for future action.
Keywords: Agriculture; Industry and Labor

Airport Emergency Communications for People with Disabilities and Others with Access and Functional Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB's Airport Cooperative Research Program (ACRP) Research Report 201 provides guidance and tools for airports to aid in effective communication with passengers and persons with disabilities, including those with cultural and language differences.The report includes a primer that discusses issues, techniques, and the unique requirements and challenges of communicating with people with disabilities and others who have access or functional needs.The report explores uses of technology and other methods that incorporate ADA considerations and communication challenges with airport stakeholders, and training programs for airport personnel, including templates for development of curricula.There are case study examples of methods of emergency communication at airports and in other industries, and for universal messaging for emergency communications.The project that produced the report also produced templates in support of airport emergency plans specifically addressing individuals with limited English proficiency, step-by-step tools that include a needs assessment tool that airports can use to determine what steps must to be taken to comply with ADA requirements concerning communications, and templates/worksheets/checklists for planning tabletop exercises that focus on communicating with people with disabilities and access or functional needs during emergency events. These resources are described and linked to below.The Inventory Checklists (from Appendix A) list plans, reports, documents, programs, and services that are helpful in emergency communications for DAFN. The checklists make it easy to review what the airport has in place, what needs to be developed or updated, etc.The Accessibility Walkthrough Worksheet (from Appendix B) is a tool to structure evaluations (ideally conducted by members of a DAFN Advisory Group, as discussed in the report) that identify and assign accessibility ratings to existing communications modes and resources from curbside through baggage claim, and identify modes or resources that can be added or improved.The FAA Airport Accessibility Checklist (from Appendix C) is reproduced online in PDF for convenience; a url is provided that directs users to the FAA source.The Accessibility Strategy Quick Reference Guide (from Appendix D) summarizes key aspects of core, enhanced, and emerging strategies described in the report.The CONOPS Template (from Appendix F) provides generic text for an Emergency Communications Concept of Operations document that airports can edit to meet their needs and those of the communities they serve.The Disability Equity Training document provides training content, including empathy exercises, from Appendix G in a format that can be adapted and customized for use by practitioners.The 1-Minute Read Poster (from Appendix H) provides a reproducible, one-page reference on how to offer and provide assistance respectfully to people with DAFN.The Outreach Brochure (also from Appendix H) is provided in a separate downloadable file for use and distribution by practitioners.The Exercise Toolkit (from Appendix I), with checklists and materials to support a discussion-based exercise and a full-scale, operational exercise, is reproduced in Word to facilitate adaptation and use by practitioners.The Prepared Scenario Vignettes (from Appendix J), which can be used to lay the foundation of a discussion-based or tabletop exercise.
Keywords: Transportation and Infrastructure

Developing an Expanded Functional Classification System for More Flexibility in Geometric Design - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's National Cooperative Highway Research Program (NCHRP) Web-Only Document 230: Developing an Expanded Functional Classification System for More Flexibility in Geometric Design, which documents the methodology of NCHRP Research Report 855: An Expanded Functional Classification System for Highways and Streets builds upon preliminary engineering of a design project, including developing the purpose and need.In particular, NCHRP Web-Only Document 230 provides additional contexts beyond urban and rural, facilitates accommodation of modes other than personal vehicles and adds overlays for transit and freight.Two case studies illustrating an application of the expanded system to actual projects are included.
Keywords: Transportation and Infrastructure

An Expanded Functional Classification System for Highways and Streets - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 855: An Expanded Functional Classification System for Highways and Streets builds upon preliminary engineering of a design project, including developing the purpose and need. In particular, it provides additional contexts beyond urban and rural, facilitates accommodation of modes other than personal vehicles and adds overlays for transit and freight. Two case studies illustrating an application of the expanded system to actual projects are included. Accompanying the report is NCHRP Web-Only Document 230: Developing an Expanded Functional Classification System for More Flexibility in Geometric Design, which documents the methodology of NCHRP Research Report 855.
Keywords: Transportation and Infrastructure

Measuring Specific Mental Illness Diagnoses with Functional Impairment: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The workshop summarized in this report was organized as part of a study sponsored by the Substance Abuse and Mental Health Services Administration (SAMHSA) and the Office of the Assistant Secretary for Planning and Evaluation of the U.S. Department of Health and Human Services, with the goal of assisting SAMHSA in its responsibilities of expanding the collection of behavioral health data in several areas. The workshop brought together experts in mental health, psychiatric epidemiology and survey methods to facilitate discussion of the most suitable measures and mechanisms for producing estimates of specific mental illness diagnoses with functional impairment. The report discusses existing measures and data on mental disorders and functional impairment, challenges associated with collecting these data in large-scale population-based studies, as well as study design and estimation options.
Keywords: Health and Medicine

Alternative Protein Sources: Balancing Food Innovation, Sustainability, Nutrition, and Health: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Alternative protein sources, which include proteins derived from plant and animal cells, and by way of precision fermentation, can have health, environmental, socio-economic, and ethical impacts. Their implications stretch across industries, sway consumer perspectives and choice, and concern regulatory policy decisions. The National Academies Food Forum hosted a workshop to explore the state of the science on alternative protein sources as they relate to issues around diet quality, nutrition, and sustainability. The workshop also examined how alternative protein food processing innovations can be balanced in a way that optimizes nutritional content, affordability, and accessibility. This Proceedings of a Workshop - In Brief summarizes the discussions held during the workshop.
Keywords: Food and Nutrition

Alternative Protein Sources: Balancing Food Innovation, Sustainability, Nutrition, and Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Alternative protein sources, which can be derived from plant and animal cells or created by precision fermentation, can have health, environmental, socio-economic, and ethical impacts. With a variety of types of alternative proteins being developed and available on the market, consumers, regulatory agencies, manufacturers, and researchers are faced with many different considerations. The National Academies Food Forum hosted a workshop that took a multi-sector approach to explore the state of the science on alternative protein sources as they relate to issues around diet quality, nutrition, and sustainability. The workshop also examined how alternative protein food processing innovations can be balanced in a way that optimizes nutritional content, affordability, and accessibility. This Proceedings of a Workshop summarizes the discussions held during the workshop.
Keywords: Food and Nutrition

A National Strategy to Reduce Food Waste at the Consumer Level - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Approximately 30 percent of the edible food produced in the United States is wasted and a significant portion of this waste occurs at the consumer level. Despite food's essential role as a source of nutrients and energy and its emotional and cultural importance, U.S. consumers waste an estimated average of 1 pound of food per person per day at home and in places where they buy and consume food away from home. Many factors contribute to this waste—consumers behaviors are shaped not only by individual and interpersonal factors but also by influences within the food system, such as policies, food marketing and the media. Some food waste is unavoidable, and there is substantial variation in how food waste and its impacts are defined and measured. But there is no doubt that the consequences of food waste are severe: the wasting of food is costly to consumers, depletes natural resources, and degrades the environment. In addition, at a time when the COVID-19 pandemic has severely strained the U.S. economy and sharply increased food insecurity, it is predicted that food waste will worsen in the short term because of both supply chain disruptions and the closures of food businesses that affect the way people eat and the types of food they can afford.
Keywords: Behavioral and Social Sciences; Food and Nutrition

The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics Related to Food and Nutrition Research: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Food and Nutrition Board hosted a hybrid public workshop in October 2023 to explore opportunities and challenges related to applying advanced computation, big data analytics, and high-performance computing, including artificial intelligence, machine learning, and deep learning, to support advances in food systems and nutrition research. Speakers discussed the appropriate use of evidence generated from these methods to inform food- and nutrition-related programs and policies.
Keywords: Food and Nutrition; Computers and Information Technology

Approaches to Assessing Intake of Food and Dietary Supplements in Pregnant Women and Children 2 to 11 Years of Age: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
A virtual workshop series titled Approaches to Assessing Intake of Food and Dietary Supplements in Pregnant Women and Children 2 to 11 Years of Age was convened in May, 2021 by the Food and Nutrition Board of the National Academies of Sciences, Engineering, and Medicine. The four-day workshop series explored the evidence on methodological approaches to assessing intake of food and dietary supplements in pregnant women and children 2 to 11 years of age. Obtaining reliable and valid dietary intake information for these population groups is particularly difficult - in pregnancy, rapid changes in nutrient needs and dietary intakes occur, and in young children, much of dietary intake is consumed outside the home and is often misreported by the children or their proxy reporters. To advance the quality of the science in these areas, the workshop had four goals: identify the suite of current methods used in dietary assessments, including food and dietary supplements, in pregnant women and children 2 to 11 years of age; identify the methodological challenges and opportunities in improving current methods; explore methodologies in other disciplines and their application in dietary assessments in those populations; and discuss factors to consider when implementing dietary assessment tools in those populations. This publication summarizes the presentations and discussions of the workshop series.
Keywords: Food and Nutrition

The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics in Food and Nutrition Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Artificial intelligence (AI), machine learning (ML), and deep learning (DL) are promising tools that can be used to develop algorithms to better understand and predict interactions between food- and nutrition-related data and health outcomes. Understanding that additional research is needed to identify areas where AI/ML is likely to have an impact, the National Academies Food and Nutrition Board hosted a public workshop in October 2023 to explore the future benefits and limitations of integrating big data and AI/ML tools into nutrition research. Participants also discussed issues related to diversity, equity, inclusion, bias, and privacy and the appropriate use of evidence generated from these new methods.
Keywords: Food and Nutrition; Computers and Information Technology

Stronger Food and Drug Regulatory Systems Abroad - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Ensuring the safety of food and the quality and safety of medicines in a country is an important role of government, made more complicated by global manufacturing and international trade. By recent estimates, unsafe food kills over 400,000 people a year, a third of them children under 5, mostly in low- and middle-income countries; every year poor quality medicines cause about 70,000 excess deaths from childhood pneumonia and roughly 8,500 to 20,000 malaria deaths in sub-Saharan Africa alone. The Federal Drug Administration (FDA) Office of Global Policy and Strategy is charged with improving capacity of the agency's foreign counterpart offices and increasing understanding of the importance of regulatory systems for public health, development, and trade. At the request of the FDA, this study sets out a strategy to support good quality, wholesome food and safe, effective medical products around the world. Its goal is to build on the momentum for strengthening regulatory systems and to set a course for sustainability and continued progress. The 2012 report Ensuring Safe Food and Medical Products Through Stronger Regulatory Systems Abroad outlined strategies to secure international supply chains, emphasized capacity building and support for surveillance in low- and middle-income countries, and explored ways to facilitate work sharing among food and medical product regulatory agencies. This new study assess progress made and the current regulatory landscape.
Keywords: Food and Nutrition; Health and Medicine

Planning Freight-Efficient Land Uses: Methodology, Strategies, and Tools - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Land-use planning is essential to fostering quality of life and harmony among the myriad social and economic activities that take place and compete for space in urban and metropolitan areas. Land-use planning also profoundly affects the commercial supply chains that deliver the goods and services that constitute urban and regional economies, and contribute to the quality of life. The TRB National Cooperative Highway Research Program's NCHRP Research Report 998: Planning Freight-Efficient Land Uses: Methodology, Strategies, and Tools is designed to prepare practitioners to make land-use decisions that minimize the private and external costs associated with the production, transportation, and consumption of goods by providing them with the tools needed to analyse the freight efficiency of current and future land uses in their jurisdictions, and identify and select land-use and transportation initiatives. Supplemental to the report are a tool for assessment of the overall impacts of freight land uses, a document about the research effort, and a presentation.
Keywords: Transportation and Infrastructure

Ensuring Safe Foods and Medical Products Through Stronger Regulatory Systems Abroad - Institute of Medicine (The National Academies Press, 2012)
A very high portion of the seafood we eat comes from abroad, mainly from China and Southeast Asia, and most of the active ingredients in medicines we take originate in other countries. Many low- and middle-income countries have lower labor costs and fewer and less stringent environmental regulations than the United States, making them attractive places to produce food and chemical ingredients for export. Safe Foods and Medical Products Through Stronger Regulatory Systems Abroad explains that the diversity and scale of imports makes it impractical for U.S. Food and Drug Administration (FDA) border inspections to be sufficient to ensure product purity and safety, and incidents such as American deaths due to adulterated heparin imported from China propelled the problem into public awareness. The Institute of Medicine Committee on Strengthening Core Elements of Regulatory Systems in Developing Countries took up the vital task of helping the FDA to cope with the reality that so much of the food, drugs, biologics, and medical products consumed in the United States originate in countries with less-robust regulatory systems. Ensuring Safe Foods and Medical Products Through Stronger Regulatory Systems Abroad describes the ways the United States can help strengthen regulatory systems in low and middle income countries and promote cross-border partnerships - including government, industry, and academia - to foster regulatory science and build a core of regulatory professionals. This report also emphasizes an array of practical approaches to ensure sound regulatory practices in today's interconnected world.
Keywords: Food and Nutrition; Health and Medicine

Practices for Integrated Flood Prediction and Response Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
State departments of transportation (DOTs) and other state and local agencies have implemented integrated flood warning and response systems to mitigate the effects of floods. These systems are critical for staging personnel, deciding when to close roads, inspecting bridges, tracking floods throughout the state, and planning recovery.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 573: Practices for Integrated Flood Prediction and Response Systems documents an overview of the state of the practice from agencies involved in finding new or innovative ways to improve flood management and response systems.Supplementary to the report is Appendix F, which includes sample documents of practices related to integrated flood prediction and response systems.
Keywords: Transportation and Infrastructure

Guidebook for Understanding Urban Goods Movement - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 14: Guidebook for Understanding Urban Goods Movement is designed to help facilitate decisions that accommodate and expedite urban goods movement while minimizing the environmental impact and community consequences of goods movement.The guidebook and cases studies are designed to help decision makers better understand the potential impacts of their urban goods movement decisions on transportation infrastructure and operations; land use and site design; and laws, regulations, and ordinances applicable to urban areas.The guidebook includes case studies that explore how urban supply chains connect to the urban economy, infrastructure, and land use patterns; their impacts on land use codes and regulations governing metropolitan goods movement of private-sector freight providers; and planning strategies for potentially improving mobility and access for goods movements in urban areas.The print version of the NCFRP Report 14 includes a CD-ROM that includes a report and appendices on the process that developed the guidebook, and two PowerPoint presentations with speaker notes that transportation planners may use to help explain how local decision makers might enhance mobility and access for goods movement in their area.The CD-ROM is also available for download as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)An article on NCFRP Report 14 was published in the January-February 2013 version of the TR News.CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Innovations in the Food System: Exploring the Future of Food: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On August 7-8, 2019, the Food Forum of the National Academies of Sciences, Engineering, and Medicine hosted a public workshop in Washington, DC, to review the status of current and emerging knowledge about innovations for modern food systems and the extent to which they are or could be designed to optimize environmental, health, social, and economic outcomes. The workshop included a broad look at food systems, case studies in food system evolution from the federal government and private sector,and sessions that focused on game-changing innovations and their implications for food systems. This Proceedings of a Workshop-in Brief summarizes the key points made by workshop participants during the presentations and discussions
Keywords: Food and Nutrition

A Framework for Assessing Effects of the Food System - Institute of Medicine; National Research Council (The National Academies Press, 2015)
How we produce and consume food has a bigger impact on Americans' well-being than any other human activity. The food industry is the largest sector of our economy; food touches everything from our health to the environment, climate change, economic inequality, and the federal budget. From the earliest developments of agriculture, a major goal has been to attain sufficient foods that provide the energy and the nutrients needed for a healthy, active life. Over time, food production, processing, marketing, and consumption have evolved and become highly complex. The challenges of improving the food system in the 21st century will require systemic approaches that take full account of social, economic, ecological, and evolutionary factors. Policy or business interventions involving a segment of the food system often have consequences beyond the original issue the intervention was meant to address. A Framework for Assessing Effects of the Food System develops an analytical framework for assessing effects associated with the ways in which food is grown, processed, distributed, marketed, retailed, and consumed in the United States. The framework will allow users to recognize effects across the full food system, consider all domains and dimensions of effects, account for systems dynamics and complexities, and choose appropriate methods for analysis. This report provides example applications of the framework based on complex questions that are currently under debate: consumption of a healthy and safe diet, food security, animal welfare, and preserving the environment and its resources. A Framework for Assessing Effects of the Food System describes the U.S. food system and provides a brief history of its evolution into the current system. This report identifies some of the real and potential implications of the current system in terms of its health, environmental, and socioeconomic effects along with a sense for the complexities of the system, potential metrics, and some of the data needs that are required to assess the effects. The overview of the food system and the framework described in this report will be an essential resource for decision makers, researchers, and others to examine the possible impacts of alternative policies or agricultural or food processing practices.
Keywords: Food and Nutrition; Agriculture

Nutrition Standards for Foods in Schools: Leading the Way Toward Healthier Youth - Institute of Medicine (The National Academies Press, 2007)
Food choices and eating habits are learned from many sources. The school environment plays a significant role in teaching and modeling health behaviors. For some children, foods consumed at school can provide a major portion of their daily nutrient intake. Foods and beverages consumed at school can come from two major sources: (1) Federally funded programs that include the National School Lunch Program (NSLP), the School Breakfast Program (SBP), and after-school snacks and (2) competitive sources that include vending machines, &#34a la carte&#34 sales in the school cafeteria, or school stores and snack bars.
Keywords: Food and Nutrition; Health and Medicine

Providing Healthy and Safe Foods As We Age: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Does a longer life mean a healthier life? The number of adults over 65 in the United States is growing, but many may not be aware that they are at greater risk from foodborne diseases and their nutritional needs change as they age. The IOM's Food Forum held a workshop October 29-30, 2009, to discuss food safety and nutrition concerns for older adults.
Keywords: Food and Nutrition; Health and Medicine

Mendel in the Kitchen: A Scientist's View of Genetically Modified Foods - Fedoroff, Nina V.; Brown, Nancy Marie (The National Academies Press, 2004)
While European restaurants race to footnote menus, reassuring concerned gourmands that no genetically modified ingredients were used in the preparation of their food, starving populations around the world eagerly await the next harvest of scientifically improved crops. Mendel in the Kitchen provides a clear and balanced picture of this tangled, tricky (and very timely) topic. Any farmer you talk to could tell you that we've been playing with the genetic makeup of our food for millennia, carefully coaxing nature to do our bidding. The practice officially dates back to Gregor Mendel -- who was not a renowned scientist, but a 19th century Augustinian monk. Mendel spent many hours toiling in his garden, testing and cultivating more than 28,000 pea plants, selectively determining very specific characteristics of the peas that were produced, ultimately giving birth to the idea of heredity -- and the now very common practice of artificially modifying our food. But as science takes the helm, steering common field practices into the laboratory, the world is now keenly aware of how adept we have become at tinkering with nature --which in turn has produced a variety of questions. Are genetically modified foods really safe? Will the foods ultimately make us sick, perhaps in ways we can't even imagine? Isn't it genuinely dangerous to change the nature of nature itself? Nina Fedoroff, a leading geneticist and recognized expert in biotechnology, answers these questions, and more. Addressing the fear and mistrust that is rapidly spreading, Federoff and her co-author, science writer Nancy Brown, weave a narrative rich in history, technology, and science to dispel myths and misunderstandings. In the end, Fedoroff arues, plant biotechnology can help us to become better stewards of the earth while permitting us to feed ourselves and generations of children to come. Indeed, this new approach to agriculture holds the promise of being the most environmentally conservative way to increase our food supply.
Keywords: Explore Science; Biology and Life Sciences

Data and Research to Improve the U.S. Food Availability System and Estimates of Food Loss: A Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2015)
The United States Department of Agriculture's (USDA's) Economic Research Service's (ERS) Food Availability Data System includes three distinct but related data series on food and nutrient availability for consumption. The data serve as popular proxies for actual consumption at the national level for over 200 commodities (e.g., fresh spinach, beef, and eggs). The core Food Availability (FA) data series provides data on the amount of food available, per capita, for human consumption in the United States with data back to 1909 for many commodities. The Loss-Adjusted Food Availability (LAFA) data series is derived from the FA data series by adjusting for food spoilage, plate waste, and other losses to more closely approximate 4 actual intake. The LAFA data provide daily estimates of the per capita availability amounts adjusted for loss (e.g., in pounds, ounces, grams, and gallons as appropriate), calories, and food pattern equivalents (i.e., "servings") of the five major food groups (fruit, vegetables, grains, meat, and dairy) available for consumption plus the amounts of added sugars and sweeteners and added fats and oils available for consumption. This fiscal year, as part of its initiative to systematically review all of its major data series, ERS decided to review the FADS data system. One of the goals of this review is to advance the knowledge and understanding of the measurement and technical aspects of the data supporting FADS so the data can be maintained and improved. Data and Research to Improve the U.S. Food Availability System and Estimates of Food Loss is the summary of a workshop convened by the Committee on National Statistics of the National Research Council and the Food and Nutrition Board of the Institute of Medicine to advance knowledge and understanding of the measurement and technical aspects of the data supporting the LAFA data series so that these data series and subsequent food availability and food loss estimates can be maintained and improved. The workshop considered such issues as the effects of termination of selected Census Bureau and USDA data series on estimates for affected food groups and commodities; the potential for using other data sources, such as scanner data, to improve estimates of food availability; and possible ways to improve the data on food loss at the farm and retail levels and at restaurants. This report considers knowledge gaps, data sources that may be available or could be generated to fill gaps, what can be learned from other countries and international organizations, ways to ensure consistency of treatment of commodities across series, and the most promising opportunities for new data for the various food availability series.
Keywords: Behavioral and Social Sciences; Food and Nutrition; Agriculture; Surveys and Statistics

Spurring Innovation in Food and Agriculture: A Review of the USDA Agriculture and Food Research Initiative Program - National Research Council (The National Academies Press, 2014)
The United States embarked on bold polices to enhance its food and agricultural system during the last half of the 19th century, investing first in the education of people and soon thereafter in research and discovery programs aimed at acquiring new knowledge needed to address the complex challenges of feeding a growing and hungry nation. Those policies, sustained over 125 years, have produced the most productive and efficient agricultural and food system in history. The U.S. Department of Agriculture (USDA) is the primary agency responsible for supporting innovations and advances in food and agriculture. USDA funds are allocated to support research through several mechanisms, including the Agriculture and Food Research Initiative (AFRI). In 2008, Congress replaced USDA's National Research Initiative with AFRI, creating USDA's flagship competitive research grants program, and the 2008 Food, Conservation, and Energy Act, known as the Farm Bill, outlined the structure of the new program. Spurring Innovation in Food and Agriculture assesses the effectiveness of AFRI in meeting the goals laid out by Congress and its success in advancing innovations and competitiveness in the U.S. food and agriculture system. Spurring Innovation in Food and Agriculture evaluates the value, relevance, quality, fairness, and flexibility of AFRI. This report also considers funding policies and mechanisms and identifies measures of the effectiveness and efficiency of AFRI's operation. The study examines AFRI's role in advancing science in relation to other research and grant programs inside of USDA as well as how complementary it is to other federal research and development programs. The findings and conclusions of this report will help AFRI improve its functions and effectiveness in meeting its goals and outcomes.
Keywords: Agriculture; Food and Nutrition

Methodologies to Estimate the Economic Impacts of Disruptions to the Goods Movement System - Transportation Research Board (The National Academies Press, 2012)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 732: Methodologies to Estimate the Economic Impacts of Disruptions to the Goods Movement System describes the impacts of bottlenecks and interruptions to the flow of goods through the nation’s major freight corridors and intermodal connectors, the dynamics of that flow in response to disruptions, and the full economic impact on public and private entities beyond just the critical infrastructure and the carriers that depend on that flow.
Keywords: Transportation and Infrastructure

Tying Flood Insurance to Flood Risk for Low-Lying Structures in the Floodplain - National Research Council (The National Academies Press, 2015)
Floods take a heavy toll on society, costing lives, damaging buildings and property, disrupting livelihoods, and sometimes necessitating federal disaster relief, which has risen to record levels in recent years. The National Flood Insurance Program (NFIP) was created in 1968 to reduce the flood risk to individuals and their reliance on federal disaster relief by making federal flood insurance available to residents and businesses if their community adopted floodplain management ordinances and minimum standards for new construction in flood prone areas. Insurance rates for structures built after a flood plain map was adopted by the community were intended to reflect the actual risk of flooding, taking into account the likelihood of inundation, the elevation of the structure, and the relationship of inundation to damage to the structure. Today, rates are subsidized for one-fifth of the NFIP's 5.5 million policies. Most of these structures are negatively elevated, that is, the elevation of the lowest floor is lower than the NFIP construction standard. Compared to structures built above the base flood elevation, negatively elevated structures are more likely to incur a loss because they are inundated more frequently, and the depths and durations of inundation are greater. Tying Flood Insurance to Flood Risk for Low-Lying Structures in the Floodplain studies the pricing of negatively elevated structures in the NFIP. This report review current NFIP methods for calculating risk-based premiums for these structures, including risk analysis, flood maps, and engineering data. The report then evaluates alternative approaches for calculating risk-based premiums and discusses engineering hydrologic and property assessment data needs to implement full risk-based premiums. The findings and conclusions of this report will help to improve the accuracy and precision of loss estimates for negatively elevated structures, which in turn will increase the credibility, fairness, and transparency of premiums for policyholders.
Keywords: Math, Chemistry, and Physics; Earth Sciences; Surveys and Statistics

Joint Development Agreements Using FTA Funds or FTA-Funded Assets - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
In the United States, transit oriented development (TOD) is now recognized as a critical element in the planning, development, and execution of transit projects. Recent legislation has been designed to streamline the approval processes for new transportation projects, focus more on safety, and establish new programs to advance critical freight projects.The TRB Transit Cooperative Research Program's TCRP Legal Research Digest 56: Joint Development Agreements Using FTA Funds or FTA-Funded Assets aims to clarify the Federal Transit Administration (FTA) assisted joint development process and attempts to separate public perceptions (and misperceptions) about TOD from reality. It is an update to TCRP Legal Research Digest 12:The Zoning and Real Estate Implications of Transit-Oriented Development.Appendix C incudes sample model agreement forms, developed from Washington Area Transit Authority’s Office of Real Estate and Station Planning Templates.
Keywords: Transportation and Infrastructure

Considerations for Returning Individual Genomic Results from Population-Based Surveys: Focus on the National Health and Nutrition Examination Survey: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Population surveys collect information from participants by asking questions. Today, many surveys also collect biologic specimens that can be used to analyze a respondents DNA and other biomarkers. The National Health and Nutrition Examination Survey (NHANES) is a population survey that also administers a physical examination, collects biospecimens, and reports some test results (e.g., cholesterol levels) to the participant. While visiting communities large and small throughout the country, NHANES collects health and nutrition data from a representative sample of individuals through in-person interviews and health examinations that take place at special mobile examination centers. The examination component consists of medical, dental, and physiological examinations, as well as laboratory tests. On December 2, 7, and 8, 2022, a workshop was convened to focus on anticipated future collections of genomic data by NHANES. The 2022 workshop explored ethical considerations and current practices for returning genomic information from active research and population surveys. This Proceedings of a Workshop summarizes the presentations and discussions at the workshop.
Keywords: Behavioral and Social Sciences

Roots and Trajectories of Violent Extremism and Terrorism: A Cooperative Program of the U.S. National Academy of Sciences and the Russian Academy of Sciences (1995-2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
During the past 25 years, the U.S. National Academies of Sciences, Engineering, and Medicine, in collaboration with the Russian Academy of Sciences, have carried out a wide variety of activities to improve understanding of the challenges in containing and reducing ethnic conflicts, violent extremism, and terrorism. Roots and Trajectories of Violent Extremism and Terrorism provides an overview of this cross-ocean program, which has involved American and Russian scientists, engineers, and medical professionals from a large number of government agencies, leading research institutions, think tanks, educational institutions, analytical centers, and consulting and commercial firms in the two countries. This report highlights challenges addressed by the academies over many years that remain of current interest as the U.S., Russian, and other governments continue to cope with old and new forms of aggression that threaten the livelihood of populations at home and abroad.
Keywords: Conflict and Security Issues

Tools for Assuring WIM Data Quality: Practical Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Weigh-in-motion (WIM) systems provide an estimate of the static weight of moving vehicles. WIM data is used for transportation and freight planning, pavement and bridge design, and highway safety investigations. NCHRP Research Report 1070: Tools for Assuring WIM Data Quality: Practical Guide, from TRB's National Cooperative Highway Research Program, provides state departments of transportation with new procedures to help practitioners improve accuracy and increase the reliability of WIM data. Supplemental to the report are NCHRP Web-Only Document 370: LTPP Data Analysis: Practical Tools and Procedures to Improve WIM Data Quality and six Excel spreadsheet tools.
Keywords: Transportation and Infrastructure

Shared-Risk Insurance Pools for Transit Agencies: A Guide (The National Academies Press, 2023)
Transit agencies are finding it increasingly difficult to find, purchase, and maintain adequate and affordable insurance coverage for public transit vehicles. The number of smaller insurance providers is decreasing due to the volatile nature and demands of the insurance industry and insurance coverage requirements in general. NCHRP Research Report 1079: Shared-Risk Insurance Pools for Transit Agencies: A Guide, from TRB's National Cooperative Highway Research Program, explains how insurance pools function, how to evaluate the feasibility of a shared-risk insurance pool, and how to establish and manage this type of pool. Supplemental to report is a presentation and NCHRP Web-Only Document 374: Developing a Guide to Shared-Risk Insurance Pools for Transit Agencies: Conduct of Research Report.
Keywords: Transportation and Infrastructure

Novel Molecular Targets for Mood Disorders and Psychosis: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Mood disorders - including depression and bipolar disorder - are common, disabling, and potentially lethal disorders, characterized by a shortened lifespan from comorbid medical illness and rising suicide rates. Medications for these conditions have been shown to be insufficiently effective in the majority of people who take them, and there remains a tremendous unmet medical need. Recent advances towards understanding the mechanisms of action for psychiatric medicines have led to the identification of potential novel molecular targets and agents for treating mood disorders. While these promising avenues for further investigation have re-energized scientific research in this area, many open questions remain. In response to this interest, the National Academies of Sciences, Engineering, and Medicine's Forum on Neuroscience and Nervous System Disorders convened a workshop in March 2021, Novel Molecular Targets for Mood Disorders and Psychosis. The goal of this workshop was to explore the landscape of novel pharmacologic treatments for psychiatric disorders, review the challenges and opportunities that have been highlighted by the development of recently approved drugs, and reflect on how to apply those lessons learned towards current and future efforts to identify and validate additional novel molecular targets. With a grounding in the personal experiences of patients living with depression and schizophrenia, workshop participants discussed the scientific, clinical, technological, regulatory, and ethical considerations of this topic. Examples of drug classes discussed in the workshop include antagonists for NMDA (N-methyl-D-aspartate) receptors and GABA (gamma-aminobutyric acid) receptors, as well as modulators for muscarinic and serotonergic receptors. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Guide for Integrating Goods and Services Movement by Commercial Vehicles in Smart Growth Environments - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 844: Guide for Integrating Goods and Services Movement by Commercial Vehicles in Smart Growth Environments describes policy, planning, design, and operations practices considering the coexistence of moving goods and services in smart growth environments at both the design and implementation stages as well as retroactively improving existing conditions. This report will help readers understand common issues and conflicts pertaining to smart growth, how those issues and conflicts manifest themselves in different environments, and the types of strategies and actions stakeholders can take to better integrate goods and services movement by commercial vehicles in smart growth environments.The report also presents the results of six case studies, each of which addresses one of the following Smart Growth classifications: industrial areas transitioning to housing and entertainment districts, working waterfronts transitioning to mixed-use and/or recreation, older commercial and neighborhood areas being revitalized, retrofitting aging commercial corridors, greenfield new communities, and large-scale reconstruction.
Keywords: Transportation and Infrastructure

Enhancing Food Safety: The Role of the Food and Drug Administration - Institute of Medicine; National Research Council (The National Academies Press, 2010)
Recent outbreaks of illnesses traced to contaminated sprouts and lettuce illustrate the holes that exist in the system for monitoring problems and preventing foodborne diseases. Although it is not solely responsible for ensuring the safety of the nation's food supply, the U.S. Food and Drug Administration (FDA) oversees monitoring and intervention for 80 percent of the food supply. The U.S. Food and Drug Administration's abilities to discover potential threats to food safety and prevent outbreaks of foodborne illness are hampered by impediments to efficient use of its limited resources and a piecemeal approach to gathering and using information on risks. Enhancing Food Safety: The Role of the Food and Drug Administration, a new book from the Institute of Medicine and the National Research Council, responds to a congressional request for recommendations on how to close gaps in FDA's food safety systems. Enhancing Food Safety begins with a brief review of the Food Protection Plan (FPP), FDA's food safety philosophy developed in 2007. The lack of sufficient detail and specific strategies in the FPP renders it ineffectual. The book stresses the need for FPP to evolve and be supported by the type of strategic planning described in these pages. It also explores the development and implementation of a stronger, more effective food safety system built on a risk-based approach to food safety management. Conclusions and recommendations include adopting a risk-based decision-making approach to food safety; creating a data surveillance and research infrastructure; integrating federal, state, and local government food safety programs; enhancing efficiency of inspections; and more. Although food safety is the responsibility of everyone, from producers to consumers, the FDA and other regulatory agencies have an essential role. In many instances, the FDA must carry out this responsibility against a backdrop of multiple stakeholder interests, inadequate resources, and competing priorities. Of interest to the food production industry, consumer advocacy groups, health care professionals, and others, Enhancing Food Safety provides the FDA and Congress with a course of action that will enable the agency to become more efficient and effective in carrying out its food safety mission in a rapidly changing world.
Keywords: Food and Nutrition; Health and Medicine

Safety of Genetically Engineered Foods: Approaches to Assessing Unintended Health Effects - Institute of Medicine; National Research Council (The National Academies Press, 2004)
Assists policymakers in evaluating the appropriate scientific methods for detecting unintended changes in food and assessing the potential for adverse health effects from genetically modified products. In this book, the committee recommended that greater scrutiny should be given to foods containing new compounds or unusual amounts of naturally occurring substances, regardless of the method used to create them.
Keywords: Biology and Life Sciences

Leveraging Food Technology for Obesity Prevention and Reduction Efforts: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Obesity is a major public health challenge. More than one-third of the U.S. adult population is considered obese, a figure that has more than doubled since the mid-1970s. Among children, obesity rates have more than tripled over the same period. Not only is obesity associated with numerous medical complications, but it incurs significant economic cost. At its simplest, obesity is a result of an energy imbalance, with obese (and overweight) people consuming more energy (calories) than they are expending.
Keywords: Food and Nutrition

Review of WIC Food Packages: Improving Balance and Choice: Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) began 40 years ago as a pilot program and has since grown to serve over 8 million pregnant women, and mothers of and their infants and young children. Today the program serves more than a quarter of the pregnant women and half of the infants in the United States, at an annual cost of about $6.2 billion. Through its contribution to the nutritional needs of pregnant, breastfeeding, and post-partum women; infants; and children under 5 years of age; this federally supported nutrition assistance program is integral to meeting national nutrition policy goals for a significant portion of the U.S. population.
Keywords: Food and Nutrition

Child and Adult Care Food Program: Aligning Dietary Guidance for All - Institute of Medicine (The National Academies Press, 2011)
The Child and Adult Care Food Program (CACFP) is a federally-funded program designed to provide healthy meals and snacks to children and adults while receiving day care at participating family day care homes, traditional child care centers, afterschool facilities, adult care facilities, and emergency shelters. CACFP has the broadest scope of any of the U.S. Department of Agriculture (USDA) food program, serving more than 3 million children and 114,000 adults across the nation. To receive reimbursement for the foods served, participating programs must abide by requirements set by the USDA.
Keywords: Food and Nutrition; Health and Medicine

Review of WIC Food Packages: Proposed Framework for Revisions: Interim Report - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) began 40 years ago as a pilot program and has since grown to serve over 8 million pregnant women, and mothers of and their infants and young children. Today the program serves more than a quarter of the pregnant women and half of the infants in the United States, at an annual cost of about $6.2 billion. Through its contribution to the nutritional needs of pregnant, breastfeeding, and post-partum women; infants; and children under 5 years of age; this federally supported nutrition assistance program is integral to meeting national nutrition policy goals for a significant portion of the U.S. population. To assure the continued success of the WIC, Congress mandated that the Food and Nutrition Service of the U.S. Department of Agriculture (USDA) reevaluate the program's food packages every 10 years. In 2014, the USDA asked the Institute of Medicine to undertake this reevaluation to ensure continued alignment with the goals of the Dietary Guidelines for Americans. This, the second report of this series, provides a summary of the work of phase I of the study, and serves as the analytical underpinning for phase II in which the committee will report its final conclusions and recommendations.
Keywords: Food and Nutrition

Sustainable Diets: Food for Healthy People and a Healthy Planet: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
One of the many benefits of the U.S. food system is a safe, nutritious, and consistent food supply. However, the same system also places significant strain on land, water, air, and other natural resources. A better understanding of the food-environment synergies and trade-offs associated with the U.S. food system would help to reduce this strain. Many experts would like to use that knowledge to develop dietary recommendations on the basis of environmental as well as nutritional considerations. But identifying and quantifying those synergies and trade-offs, let alone acting on them, is a challenge in and of itself. The difficulty stems in part from the reality that experts in the fields of nutrition, agricultural science, and natural resource use often do not regularly collaborate with each other, with the exception of some international efforts. Sustainable Diets is the summary of a workshop convened by The Institute of Medicine's Food Forum and Roundtable on Environmental Health Sciences, Research, and Medicine in May 2013 to engender dialogue between experts in nutrition and experts in agriculture and natural resource sustainability and to explore current and emerging knowledge on the food and nutrition policy implications of the increasing environmental constraints on the food system. Experts explored the relationship between human health and the environment, including the identification and quantification of the synergies and trade-offs of their impact. This report explores the role of the food price environment and how environmental sustainability can be incorporated into dietary guidance and considers research priorities, policy implications, and drivers of consumer behaviors that will enable sustainable food choices.
Keywords: Food and Nutrition; Health and Medicine

Reducing Impacts of Food Loss and Waste: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Even as malnutrition in the form of hunger and obesity affect the health and well-being of millions of people worldwide, a significant amount of food is lost or wasted every day, in every country, and at every stage in the supply chain from the farm to the household. According to a 2011 estimate by the Food and Agriculture Organization of the United Nations (FAO), about one-third of food produced is lost or wasted globally. Beyond quantity estimates, however, less is known about the impacts on farmers, food prices, food availability, and environment of reducing food loss and waste.
Keywords: Food and Nutrition